2008
DOI: 10.1016/j.yexmp.2007.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Foreign body-type multinucleated giant cell formation requires protein kinase C β, δ, and ζ

Abstract: Multinucleated giant cells are a classic cellular feature of chronic inflammation, although the mechanism of macrophage fusion leading to their formation is not well understood. Here, we investigate the participation of protein kinase C (PKC) in the interleukin (IL)-4-induced fusion of human monocyte-derived macrophages and foreign body giant cell (FBGC) formation in vitro. The PKC inhibitors H-7 and calphostin C attenuated macrophage fusion, whereas H-8, which is more selective for PKA and PKG, did not. Macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…), and foreign‐body induced multinucleation of macrophages is known to be mediated by PKCs (McNally et al . ). Thus, inflammatory agents might cause multinucleation of microglia via stimulation of PKCs.…”
Section: Discussionmentioning
confidence: 97%
“…), and foreign‐body induced multinucleation of macrophages is known to be mediated by PKCs (McNally et al . ). Thus, inflammatory agents might cause multinucleation of microglia via stimulation of PKCs.…”
Section: Discussionmentioning
confidence: 97%
“…The use of the PKCβ inhibitor Gö 6983 that acts avoiding phosphorylation of several PKC isoforms, including PKCβ [29], provoked a decrease in the Wnt pathway components, GSK3β serine phosphorylation and β-catenin, concomitant with an increase in the expression of the differentiation markers, indicating the relationship between PKCβ and Wnt pathway in this process.…”
Section: Discussionmentioning
confidence: 99%
“…Anderson and colleagues showed that macrophage fusion induced by interleukin‐4 (IL‐4) is dependant on activity of the mannose receptor, a classical phagocytic mediator,8 though it should be noted that phagocytosis in macrophages can be mediated by a number of different mechanisms 9, 10. Furthermore, this group has established extensive homology between phagocytosis and fusion in endoplasmic reticulum function,11 response to vitronectin expression,12 and downstream kinase signaling activity 13. Others have shown that FBGC can engulf large foreign bodies in a phagocytic‐like manner14 and that macrophages that have phagocytosed particles are capable of fusion in the context of osteoclastic differentiation 15.…”
Section: Introductionmentioning
confidence: 99%